Geography in Bangladesh concepts, methods and applications - Islam, Tawhidul; Paul, Alak (Routledge, 2019)
"This book provides an overview of the emergence of geography as a discipline in Bangladesh and the contributions made by local geographers towards the development of the country. It explores problems associated with population growth and poverty, landlessness and food security, land use and natural resource management, urbanism, climate change, disaster management, and human health. The volume shows how research and the study of geography in the 'periphery' can contribute in achieving progress in countries like Bangladesh and help them prepare against imminent disasters, ecological, social, economic shocks and uncertainties. This book will be useful to students and researchers of geography, environment studies, disaster management, development studies, geo-informatics, geology, demography, and sociology and South Asian studies, with a particular focus on Bangladesh. It will also interest various policy makers and NGO professionals working in these and related fields"--